Formulation and Characterization Sunscreen Emulgel Containing Cinnamon Bark Oil (Cinnamomum Burmannii Nees Ex Blume) - Priani, Sani Ega (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Cinnamon bark oil is known to contain high levels of cinnamaldehyde (>50%). Cinnamaldehyde is an aromatic compound that is conjugated with a carbonyl group and potential to have photoprotective activity. The purpose of this study was to develop an emulgel preparation containing cinnamon bark oil and to evaluate the  emulgel in terms of its physical properties, stability, and sunscreen activity. Cinnamon bark oil was characterized based on SNI 06-3734-2006. Cinnamon bark oil at concentrations of 0.5 and 1 % was formulated into an emulgel using a combination of stearic acid and triethanolamine as an emulsifier and viscolam mac 10 as a gelling agent. The preparation was evaluated for its physical characteristics and stability. The sunscreen activity test was carried out in vitro by determining the Sun Protection Factor's values (SPF), % erythema, and % pigmentation.  The results showed that cinnamon oil met the SNI standards of cinnamaldehyde concentration (53.33 %). Cinnamon oil emulgel preparation has good physical properties in terms of organoleptic, pH, viscosity, rheology, spreadability, and stability based on centrifugation and freeze-thaw tests. The addition of 0.5 and 1% of cinnamon oil significantly increased the sunscreen activity of the emulgel based on the SPF, % erythema, and % pigmentation values with the extra protection category. An emulgel containing cinnamon bark oil has been successfully developed which has good physical properties and stability and has sunscreen activity based on the value of FPS, % erythema, and % pigmentation.